Assistance Robotics and Biosensors - Fernando Torres (Ed.)
This Special Issue is focused on breakthrough developments in the field of biosensors, as well as on the current scientific progress in biomedical signal processing. The papers address innovative solutions in assistance robotics based on bioelectrical signals, including the following: affordable biosensor technology, affordable assistive-robotics devices, new techniques in myoelectric control, and advances in brain-machine interfacing.